(untitled) (Journal of Parents and Teachers, 2014)
Kid Nation is one of the latest reality shows in US in which they leave 40 kids between 8 and 15 years old on their own in a ghost city in New Mexico. They have to build a society, elect leaders and create laws. The innovative part of this show is leaving the kids alone, but adult manipulation, who really are behind the cameras, the commercial aim and the pretended lack of surveillance make this reality a clear example of violation of kids rights.